Jesús, María and José: the Holy Family in San Pablito (1874-1970) - Peral Rabasa, Francisco J. (Onomástica desde América Latina, 2024)
To account for the presence of the names of Jesús, María and José, that is, the Holy Family in the community of San Pablito in Puebla, we will begin by discussing the introduction of these names then, we will address their manifestation in Mexican territory and subsequently shift our focus to their particular presence in San Pablito. Being three very old names due to their origin, and at the same time three of great importance, two aspects that draw our attention are: the first, the persistence of these names over time despite what trends predicted in 1970 about their possible disappearance (Boyd-Bowman 1970: 30); and the second, the disparity between them in their attribution, that is, José is by far more common than Jesús and the percentage of women named María exceeds the percentage of men with the name José. We can understand why the names have endured because the Catholic community remains the majority in Mexico, despite the constant growth of other religions. To explain the second phenomenon there are two concepts that allow us to elucidate it which are: latría and dulía.The corpus for this research is based on the information recorded in the birth books of the Civil Registry of Pahuatlán (municipal capital), during the period from 1874 to 1970, consisting of 3094 names, of which 1212 are, or include, the names: Jesús, María and/or José. The socionomastic perspective (Seide 2016, 2020) adopted allowed us to consider factors that provided meaning to the quantification and comparison of the data. Among others, variants of religious, social, political, and legal order. An example of this is the mandatory registration of births in the 40s and 50s and the consequent sanctions for those who did not comply (Peral 2023), which directly impacted the statistics.